The Prevalence and Risk Factors of Paternal Sleep Problems Across the Perinatal Period in Hong Kong - a Longitudinal Study - Koh, Yee Woen; Yesim KARAKAYA; Chui Yi Chan, Ph.D.; Catherine So-Kum Tang, Ph.D; Jean Wei-Jun Yeung, Ph.D (European Journal of Multidisciplinary Studies, 2017)
Background: The present study aimed to identify the prevalence of sleep problems among the fathers from the antenatal to postpartum period as well as their risk factors with an aim to develop strategies to assist the fathers during the transition period. Methods: A consecutive sample of 540 Chinese expectant fathers were recruited. Expectant fathers were administered a set of questionnaires at first presentation (12 weeks gestation), 36 weeks pregnancy and 6 weeks after childbirth. Sleep problems was assessed with the Pittsburgh Sleeping Quality Index (PSQI). Demographic and psychosocial risk factors were also assessed. Findings: An alarming 42.2 percent, 57.5 percent and 70.3 percent of the fathers were identified to have sleep problems at early, late pregnancy and six week postpartum respectively. Hierarchical multiple regression analysis showed that poor self-esteem and work family conflict were significant risk factors for sleep problems at early pregnancy and late pregnancy respectively, even after controlling for confounders. Poor social support and work family conflict significantly predicted sleep problems at six week postpartum. Discussions: The prevalence of sleeping problems among the fathers during perinatal period was alarmingly high and warrants serious attention. Given the potential adverse impact of sleep problems on fathers’ mental and physical health as well as caregiving abilities, findings from this study point to the need to equip fathers with psychosocial resources through perinatal psychoeducation, support group and counselling. Caution should be exercised in generalizing the results to fathers of other backgrounds as the sampling of the present study only include a certain area of Hong Kong.